Sulfuric acid recovery from rare earth sulphate solutions by diffusion dialysis - 唐建军 周康根 张启修 (Transactions of Nonferrous Metals Society of China, 2006)
Sulfuric acid recovery from rare earth sulphate solutions by diffusion dialysis was studied. The mass transfer model of diffusion dialysis was established, the comparison between the experimental results and mathematical results was carried out, and the numerical analysis on the effects of operational parameters was studied. The results indicate that the derived mathematical model shows good quantitative relation between sulphuric acid recovery ratio and operational parameters, and the mathematical results agree with the experimental results well. The numerical analysis results indicate that it is appropriate to keep the ratio of water and feed flow rates, processing capacity per membrane area and recovery ratio of sulphuric acid to be 1, 20 L/（m^2.d） and 0.7-0.8, respectively.